Pembangunan dan penilaian aplikasi pembelajaran berasaskan web dalam institusi pondok di Negeri Kedah - Saifolrudin Khalid, Mahzan (2021)
Efforts to address web technology as options in the learning process in ‘pondok’ are consistent with the needs of 21st century learning. Critical analysis revealed that the present learning style remains conventional and studies on web technology applications in ‘pondok’ inadequate. Therefore, this study examined the suitability of Islamic E-Education prototype system developed for learning purpose in ‘pondok’. This study focused on the process of the prototype system development and assessed the perceptions, attitudes and acceptance of the students and teachers towards learning via web technology. The prototype system development method was based on the ADDIE Model comprises 5 phases namely Analysis, Design, Development, Implementation and Evaluation. The prototype was initially verified by the System Evaluation Experts prior to its operation. Mixed Method Research (MMR) encompassing questionnaires and interviews were applied. Quantitative data obtained through questionnaires from 90 students was analysed using IBM SPSS software version 22.0, while qualitative data from interviews with 12 respondents was analysed thematically. The System Evaluation Experts confirmed that the prototype system is deemed suitable. Descriptive findings indicate an increase in the mean score of perception and attitude between pre and post tests. Mean score of acceptance was also very high. ANOVA and MANOVA tests found no significant difference between the students' perceptions, attitudes and acceptance based on gender and age. However, there was a significant difference between students' perceptions and attitudes based on experience and skills of ICT. The interviews revealed a high level of perception, positive attitude and very good acceptance. Hence, this study provides significant implications to the ‘pondok’ institutions which shows the integration of web technology is vital in 21st century learning. The use of web technology in learning in ‘pondok’ institutions is deemed very effective in contributing to diversifying teaching and learning methods in ‘pondok’ institutions in Kedah.